Great Expectations but Disappointing Results : What Went Wrong with the Cambodia Institute of Banking? - Biallas, Margarete O. (World Bank, Washington, DC, 2012)
There were great expectations of success in January 2004 when International Finance Corporations (IFC's) multidonor advisory initiative, the Mekong Private Sector Development Facility (MPDF) launched the Cambodia Institute of Banking (CIB), Cambodia's first training center for the finance industry. There was obvious need, the Association of Banks in Cambodia was backing CIB with members' own money, and IFC advisory staff was well qualified to help launch and advice CIB after three years of advising a similar, successful institution in Vietnam. So, with many good reasons for success, why was CIB a disappointment, and what lessons can be learned from this? Establishing business development service providers such as CIB is a good use of donor money, because many more enterprises can be served. But the approach is based on several important assumptions that should not be underestimated. The market must be large enough; financing must be sufficient; and the sponsor must be committed and provide enough funding. Also, Board members must have the right skills and enough time, and be willing to serve for several years. And in a frontier, post conflict country like Cambodia, where qualified staff is in short supply, the time frame for spin-off must be much longer.